2022
DOI: 10.1111/1467-8462.12460
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Consumer Inflation Expectations during the COVID‐19 Pandemic

Abstract: We study how individuals' formation of inflation expectations are affected by the stringent containment and economic support measures put in place during the COVID-19 pandemic. Using the New York Fed Survey of Consumer Expectations (SCE) and the Oxford COVID-19 Government Response Tracker (OxCGRT), we find that policies aimed at containing the pandemic lead to an increase in individuals' inflation expectations and inflation uncertainty. We also find some heterogeneity in the impact across different demographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 24 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…The studies based on big data ( van der Wielen & Barrios, 2021 ) compared Google search trends across the European Union countries and found that the growth of COVID-19 cases and COVID-19 related deaths contributed to the anxiety about the economy and jobs, while content analysis of Twitter feeds related to the post-lockdown plans exhibited cross-cultural differences in the preferred types of activities with individual-centric activities more frequently mentioned by users from individualistic cultures and collective activities by those from community-centric cultures ( Pantano et al, 2021 ). Observational studies based on time series analysis of data from U.S. consumers show that the pandemic contributed to the surge in uncertainty about short-term inflation and greater polarization of consumer expectations between those who perceive pandemics as deflationary and those perceiving it as inflationary without at the same time affecting the expected level of inflation ( Apergis & Apergis, 2021 ; Detmers et al, 2022 ).…”
Section: What Influences Consumer Confidence?mentioning
confidence: 99%
See 1 more Smart Citation
“…The studies based on big data ( van der Wielen & Barrios, 2021 ) compared Google search trends across the European Union countries and found that the growth of COVID-19 cases and COVID-19 related deaths contributed to the anxiety about the economy and jobs, while content analysis of Twitter feeds related to the post-lockdown plans exhibited cross-cultural differences in the preferred types of activities with individual-centric activities more frequently mentioned by users from individualistic cultures and collective activities by those from community-centric cultures ( Pantano et al, 2021 ). Observational studies based on time series analysis of data from U.S. consumers show that the pandemic contributed to the surge in uncertainty about short-term inflation and greater polarization of consumer expectations between those who perceive pandemics as deflationary and those perceiving it as inflationary without at the same time affecting the expected level of inflation ( Apergis & Apergis, 2021 ; Detmers et al, 2022 ).…”
Section: What Influences Consumer Confidence?mentioning
confidence: 99%
“…4 Cavazos examines the economic costs stemming from disinformation. 5 Our experimental design capitalizes on the above findings, as well as on the growing consensus in the consumer behavior literature that the pandemic increased uncertainty about macroeconomic trends ( Apergis & Apergis, 2021 ; Detmers et al, 2022 , Dietrich et al, 2022 ). Disinformation about the effectiveness of anti-COVID-19 vaccines is hence particularly relevant in this context.…”
Section: Disinformation and Consumer Confidence: A Conceptual Modelmentioning
confidence: 99%
“…Studies in this literature have taken different approaches, e.g. looking at how inflation expectations developed during crises/macroeconomic downturns or in relation to output and unemployment expectations (Ehrmann et al, 2017;Knotek et al, 2020;Binder, 2020;Candia et al, 2020;Detmers et al, 2022;Dietrich et al, 2022). Some papers have also gone a step further and investigated the heterogeneity of beliefs (e.g.…”
Section: Economic Sentiment and Inflation Expectationsmentioning
confidence: 99%
“…Uncertainty rose quickly in the initial period, while expectations rose moderately in the lockdown period and more notably in the reopening period. Detmers et al (2022) also use the daily SCE data to study inflation expectations in the pandemic, but their main focus is on state-level government responses to the pandemic. Containment policies aimed at mitigating the pandemic were associated with higher inflation expectations and uncertainty.…”
Section: Introductionmentioning
confidence: 99%